KEJADIAN STUNTING DALAM PERSPEKTIF IBU BALITA - Situmeang, Lamria; Kusumawardani, Emi; Pratiwi, Adelina; Utami, Utami; Rofiqoh, Rofiqoh (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Stunting is a condition where there is failure to thrive in children under five years old caused by chronic malnutrition so that children are too short for their age. Blora Regency has several areas that are included in the focus of handling stunting, one of which is the Kedungtuban area. Kedungtuban Health Center is the main health center in Kedungtuban District. The purpose of the study was to determine the causes of stunting in the perspective of mothers of toddlers. The type of research is quantitative with a cross sectional approach. The research was conducted at the Kedungtuban Health Center. The sample amounted to 94 people. The sampling technique used in this study was purposive sampling. Data analysis was done univariate and bivariate. The results showed there was a relationship between maternal knowledge (p value: 0.000) and exclusive breastfeeding (p value: 0.000) with the incidence of stunting. It is recommended for the Puskesmas to schedule routine health counseling activities for mothers of toddlers about stunting prevention and develop an assistance program to improve nutritional intake.Keywords: Exclusive Breastfeeding, Maternal Knowledge, Stunting